Using Quality Improvement to Reduce IV Acetaminophen Use in a PICU. Issue 6 (June 2020) - Howell, Katelyn A.; Ruggles, Cassandra A.; Thompson, Marlene; Metzger, Kelly Z.; Christopher, Jean A.; Bigham, Michael T.
Abstract : Objectives: Improve medication-related variable ICU costs by increasing value related to a locally identified high-frequency/high-cost medication, IV acetaminophen. Design: Structured quality improvement initiative using the Institute for Healthcare Improvement's Model for Improvement. Setting: Twenty-three–bed tertiary PICU. Patients: All patients admitted to the PICU receiving IV acetaminophen during the study period of 2015–2018. Interventions: PICU staff survey, education to close nurse/provider knowledge gap, optimization of order sets and electronic health record order entry, improving oral/enteral medication transition, and optimization of pharmacy dispensing. Measurements and Main Results: The primary outcome of interest was IV acetaminophen doses per patient day reported as a 12-month rolling average. Baseline IV acetaminophen prescribing prior to the study period was initially 0.55 doses per patient day, and in 2014, there were 3, 042 doses administered. IV acetaminophen is 43 per dose. The rolling 12-month average post intervention was 0.33 doses per patient day. Enteral and rectal doses increased from 0.42 to 0.58 doses per patient day. Opioid utilization varied throughout the study. A 40% reduction in IV acetaminophen equated to a 35, 507 cost savings in a single year. Conclusions: IV acetaminophen is prescribed with high frequency and impacts variable PICU costs. Value can be improved by optimizing IV acetaminophen prescribing.